(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
Philosophy is primarily concerned with the clarification of concepts and terms in daily usage. However, the results are different when words are concealed or shrouded within the mysterious cocoon of poetry, or if they are enwrapped in poetical rendition. This is because poems generally don’t only capture the opulent essence of existence, but utilizes the immanent tools and devices like simile, metonymy, synecdoche, metaphor, symbolisms and pun, which were lavishly utilised by Professor Sylvanus Udoidem, the PHILOSOPoet; and by which he sought to reveal the nature of GOD in his rhythmic renditions of poetry. In this work, we look at how he unleashed his philosophical defence of the authority and origin of Christianity – apologetics. The post prandial intuition portrayed by this work shows that even in retirement, the food the PHILOSOPoet prepared with his intellectual acumen/delectation has refused to whittle down, but rather continues to swell like a tidal flow, sometimes overflowing its banks, and at other times, simply cutting below the knee so that even a newt can wade across the vast acreage of his collections and philosophical sagacity. We will here seek to re-interpret and re-discover his PHILOSOPoetry in such coherent way that it would mandate GOD’s existence, prompt and promote the whole essences of the Almighty, to whom he was a wholly dedicated and served eruditely and sedately for over four decades. We will drop sail by situating his works within his calling as a Priest, Erudite Reverend Father, a philosopher par excellence and an icon, whose faith and believe remains a shining beacon of hope in a dimly lit religious verandah. This work will serves to re-establish and spur us to like, Rev. Father Prof. Udoidem, reignite our love for the spiritual and seek to know GOD with increasing fervour and motivation.